Descriptive Study of the Nominations for the 2021 Ricardo Fernández Guardia Theater National Award - Mena Young, Bernardo (2024)
Introduction: This is a descriptive study of the shows nominated for the 2021 Ricardo Fernández Guardia Theater National Award, documenting part of the theatrical events that occurred in that year. Objective: The aim is to describe the most relevant aspects of the nominated shows as observed by the researcher, based on typological, thematic, and socio-economic criteria. Methods: The shows from the corpus were observed, and notes were taken, which were later systematized in a spreadsheet according to the proposed categories. Results: For the period, the observed production displays a combination of enunciation modes and acting modalities, with women emerging as the dominant theme. At the socio-economic level, there is a limited regionalization and casts determined by access to resources. Conclusions: It is suggested that the results are associated with complex processes of sociocultural change, emphasizing the need to study theater based on increasingly comprehensive corpora.